Membangun Keberdayaan Perempuan Single Parent di Batu Hampa Kabupaten Pesisir Selatan - Lukmanul Hakim; Ahmad Syarifin; Ihsan Sanusi; Aziza Meria (Kafa`ah: Journal of Gender Studies, 2018)
This article is to describe and analyze the aspirations and needs of single parent women in the context of empowerment through religious education and entrepreneurship and to analyze patterns of empowering entrepreneurial religious education that are relevant for single parents. This research was conducted by using  Participatory Action Research (PAR). The techniques include: transects, interviews and Focus Group Discussion (FGD). Factors that cause the low management and utilization  in Batu Hampa Village are: economic factors - limited capital, and intermediary factors that facilitate and allow the rooted inability of single parent women and Low Human Resources of single parent women.